B - is for Bird - A game-audio musical work for resynthesized syrinx (ouvirOUver, 2016)
ABSTRACTBirdsongs have inspired humans and informed musical compositions and other art forms for centuries. This paper discusses preliminary conclusions deriving from the design of an interactive music system for mimicking birds' vocal anatomy. It aims to drive a modular synthesizer, as the basis for a multiplayer game-audio environment. The piece is partially controlled by audience's interaction using mobile devices equipped with an Augmented Reality tool. When the tablet / smartphone detects the markers, it generates singing meta-birds which will become players on a game-engine server platform.The creative outcome is an evolutionary aural ecosystem entitled B - is for Bird - mostly generated with pure analogue synthesis driven by birdsongs and rendered in 3D. Its premiere is aimed at the Sines-Squares(.org) event in November 2016.B's system flow includes four block components: a Syrinx Recognition Scheme (SRS), a Mapping-to-Modular Tool (MTM), a Compositional Navigation Artefact (CNA) and a Structural Evolutionary Device (SED). The piece aims to build on existing musical repertoire and tradition emerging from composers who, in one way or another, were fascinated by birds and in some cases, became amateur ornithologists. The author's preliminary field-recording work for B in Manchester's peak district's natural reservoir strengthened his personal connection with nature. It also raised his self-awareness on the importance of preserving of our sonic environment and it provided ideas for the game-audio chronicle in B. The piece's narrative unfolds during the colonisation of a new planet, where humans had to artificially rebuild aspects of our ecosystem, including the construction of a virtual habitat for meta-birds singing and calls.RESUMOCantos dos pássaros têm inspirado os seres humanos e fomentado composições musicais e outras formas de arte ao longo dos séculos. Este artigo discute algumas conclusões preliminares derivadas do desenvolvimento de um sistema musical interativo para imitar a anatomia vocal das aves. Destina-se a controlar um sintetizador modular como base para um ambiente de jogo multiplayer de áudio. A peça é parcialmente controlada pela interação do público por meio de dispositivos móveis equipados com uma ferramenta de Realidade Aumentada. Quando o tablet / smartphone detecta os marcadores, gera meta-pássaros cantadores que se tornarão jogadores em uma plataforma de servidor do jogo.O resultado criativo é um ecossistema aural evolutivo entitulado B - is for Bird - gerado principalmente com síntese analógica pura guiada por cantos de pássaros e renderizado em 3D. Sua estréia está prevista para o evento Sines-Squares(.org) em Novembro de 2016.O fluxo do sistema de B inclui quatro blocos de componentes: um Esquema de Reconhecimento de Siringe (SRS), uma Ferramenta de Mapeamento-para-Modular (MTM), um Artefato de Navegação Composicional (CNA) e um Dispositivo de Evolução Estrutural (SED). A peça tem o objetivo de construir-se sobre um repertório e uma tradição musical que emerge de compositores que, de uma forma ou de outra, foram fascinados por aves e, em alguns casos, tornaram-se ornitólogos amadores.O trabalho preliminar de gravação em campo para a composição de B, feito pelo autor no reservatório natural do Peak District de Manchester reforçou sua conexão pessoal com a natureza. Além disso, aguçou sua auto-consciência sobre a importância da preservação do nosso ambiente sonoro e forneceu idéias para a crônica do jogo de áudio em B. A narrativa da peça se desenrola durante a colonização de um novo planeta, onde os seres humanos tiveram que reconstruir artificialmente aspectos do nosso ecossistema, incluindo a construção de um habitat virtual para cantos e chamadas de meta-pássaros.